Immature electrophysiological properties of human-induced pluripotent stem cell-derived neurons transplanted into the mouse cortex for 7 weeks. Issue 3 (6th February 2019) - Kayama, Tasuku; Okamoto, Kazuki; Gao, Mengxuan; Ikegaya, Yuji; Sasaki, Takuya
Abstract : The transplantation of human-induced pluripotent stem cell (hiPSC)-derived cells has emerged as a potential clinical approach for the treatment of brain diseases. Recent studies with animal disease models have shown that hiPSC-derived neurons transplanted into the brain, especially the nigrostriatal area, could restore degenerated brain functions. Further works are required to test whether hiPSC-derived neurons can also gain functional properties for other cortical areas. In this study, hiPSC-derived neurospheres were transplanted into the adult mouse hippocampus and sensory cortex. Most transplanted hiPSC-derived neurons expressed both Nestin and NeuN at 7 weeks after transplantation. Whole-cell patch-clamp recordings from brain slices indicated that transplanted cells showed no action potentials upon current injection and few small inward currents, indicating that hiPSC-derived neurons did not become functionally mature within these time periods.